P21‐activated kinase‐2 is a critical mediator of transforming growth factor‐β‐induced hepatoma cell migration. Issue 6 (22nd May 2013) - Sato, Munehiro; Matsuda, Yasunobu; Wakai, Toshifumi; Kubota, Masayuki; Osawa, Mami; Fujimaki, Shun; Sanpei, Ayumi; Takamura, Masaaki; Yamagiwa, Satoshi; Aoyagi, Yutaka
Abstract Background and Aim Transforming growth factor‐β (TGF‐β) has been shown to play a central role in the promotion of cell motility, but its functional mechanism has remained unclear. With the aim of investigating the diagnostic and treatment modalities for patients with hepatocellular carcinoma (HCC), the signaling pathway that may contribute to TGF‐β‐mediated cell invasion in hepatoma cells was evaluated. Methods Three hepatoma cell lines, HepG2, PLC/PRF/5, and HLF, were treated with TGF‐β, and the involvement of the non‐canonical TGF‐β pathway was analyzed by cell migration assays. HepG2 cells were treated with a p21‐activated kinase‐2 (PAK2)‐targeting small interfering RNA and analyzed for their cell motility. The relationships between the PAK2 status and the clinicopathological characteristics of 62 HCC patients were also analyzed. Results The cell migration assays showed that Akt is a critical regulator of TGF‐β‐mediated cell migration. Western blotting analyses showed that TGF‐β stimulated Akt and PAK2 in all three hepatoma cell lines, and phosphorylated PAK2 was blocked by Akt inhibitor. Suppression of PAK2 expression by small interfering RNA resulted in increased focal adhesions with significantly repressed cell migration in the presence of TGF‐β. Clinicopathological analyses showed that the phosphorylation level of PAK2 was closely associated with tumor progression, metastasis, and early recurrence of HCC. Conclusions PAK2 may be a critical mediator of TGF‐β‐mediated hepatoma cell migration, and may represent a potential target for the treatment of HCC.